DETERMINATION OF INSULIN GENE INSG POLYMORPHISMS AND THEIR RELATIONSHIP WITH SOME PRODUCTIVE TRAITS IN BOTH SEXES OF HYBRID BROILER ROSS308 - & Mohamed, Al- Alanbari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To determine the polymorphisms of Insulin gene INSg and its relationship with some productive traits such as rate of initial and weekly body weight, average weekly body gain, live body weight, carcass weight, dressing %, cuts weight and weight for abdominal fat on broiler in both sexes for Ross 308 hybrid, 200 one – day old chicks, reared on closed system tagged and weighted initially and weekly for 35 days, polymorphisms for Insulin gene were determined by using MSPI restriction enzyme and PCR-RFLP technique. Results showed two genotypes were detected only for INSg differ highly significantly P<0.01 between them and on its effect on studied treats was differ significantly P≤ 0.05 for male in both genotypes also Male in heterozygous and homozygous genotype was differ on weekly body weight that caused effect on weekly body weight gain also when compared with female in each genotype. Male with TC genotype effect P<0.05 on carcass weight ,breast weight , leg weight and wing weight compared with female with same genotype, while male with TT genotype effect P<0.05 on live body weight and leg weight wing weight also when compared with female in the same genotype. That means it’s very important to use methods of molecular technique to be used as easy tool on selection programs on parent of commercial flock to select male for rearing to be guaranty reaching suitable weight and gens weight and cuts weight for hybrid.